A C-type lectin that inhibits bacterial infection and facilitates viral invasion in black rockfish, Sebastes schlegelii. (October 2016) - Liu, Yong; Li, Ning-qiu; Zhao, Xin-peng; Yue, Bin; He, Shu-wen; Gao, Zhi-xin; Zhou, Shun; Zhang, Min
Abstract: C-type lectins (CTLs) are important pattern recognition receptors (PRRs) that play vital roles in innate immunity. In teleosts, a number of CTLs have been reported, but their in vivo effects on host defense are still limited. In this study, a CTL homolog (SsLec1) was identified from black rockfish, Sebastes schlegelii, and its structure, expression and biological function was analyzed. The open reading frame of SsLec1 is 633 bp, with a 5'- untranslated region (UTR) of 36 bp and a 3′- UTR of 117 bp. The deduced amino acid sequence of SsLec1 shares the highest overall identity (73.20%) with the CTL of Oplegnathus fasciatus . SsLec1 possesses conserved CTL features, including a carbohydrate-recognition domain, four disulfide bond-forming cysteine residues, the mannose-type carbohydrate-binding motif, the conserved calcium binding sites and a putative signal peptide. The expression of SsLec1 was highest in liver and could be induced by experimental infection with Listonella anguillarum . Recombinant SsLec1 (rSsLec1) purified from E. coli was able to bind and agglutinate the Gram-negative fish pathogens Vibrio ichthyoenteri and Vibrio vulnificus . The agglutinating ability of rSsLec1 was abolished in the presence of mannose or ethylenediaminetetraacetic acid. Further analysis showed that rSsLec1 could enhance phagocytosis by macrophages. In vivo experiments indicated that rSsLec1 could inhibit bacterial infection and promote viral invasion. Taken together, these results suggest that SsLec1 is a novel CTL that possesses apparent immunoregulation property and plays a critical role in host defense against pathogens invasion. Highlights: A C-type lectin homolog (SsLec1) was identified and characterized. Expression of SsLec1 in tissues and macrophages could be induced by Listonella anguillarum. Recombinant SsLec1 purified from E. coli could recgonize and agglutinate Vibrio ichthyoenteri and Vibrio vulnificus . Recombinant SsLec1 could inhibit bacteria infection and facilitate viral infection in vivo.